Acceleration of electrons in hollow glass capillaries under the action of intense picosecond laser pulses. (September 2021) - Flegentov, V.A.; Safronov, K.V.; Gavrilov, D.S.; Kakshin, A.G.; Pkhaiko, N.A.; Potapov, A.V.
Abstract: The generation of relativistic electron beams in hollow glass capillaries is investigated using a picosecond laser system. A plasma is formed in a capillary due to the ablation of its inner walls by a specially formed pre-pulse. Electron beams with an opening angle of ∼40 mrad, exponential energy spectrum with maximum energy about 20 MeV, and a total charge of ∼0.2 nC are experimentally detected.